On salt marshes retreat: Experiments and modeling toppling failures induced by wind waves. Issue 3 (24th March 2014) - Bendoni, M.; Francalanci, S.; Cappietti, L.; Solari, L.
Abstract Salt marshes are delicate ecosystems which are disappearing in many areas of the world, mainly due to increasing rates of sea level rise, subsidence, and anthropic pressure. The lateral erosion of the edge of salt marshes is one of the most important processes in determining changes in morphology, and wind waves have a key role in this retreat. Lateral retreat occurs by means of several types of mass failure processes, typically cantilever, sliding, and toppling. In the literature, no mechanistic models for the description of toppling failure are available. In this study, we performed a set of experiments to quantify the pressure field and the hydrodynamic forcing induced by wind waves during toppling failures of unstable blocks on a salt marsh edge. We propose a model interpreting toppling failure based on the experimental evidence as well as on the physics of the system. We model the system as a dynamic rigid block of cohesive soil, identified by the presence of a tension crack, subjected to hydrodynamic forces caused by impact of waves and resistive forces due to the block's weight and soil cohesion. The failure of the blocks occurs when the soil tensile strength is exceeded along the failure surface located at the base of the block. The model is able to reproduce failure processes observed in the laboratory. Moreover, the model reveals that the most critical conditions for marsh bank instability due to toppling failure are associated to the presence of water inside the tension crack and low water levels in front of the bank.